ANALISIS PELAKSANAAN PENGAWASAN INTERNAL DI RSUD TUGUREJO PROVINSI JAWA TENGAH - Syifa Nur Fadhilah; Septo Pawelas Arso; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2019)
On providing health services Hospital chance to be prone of deviation in the presence of health services especially finance and assets management it can cause the hospital difficult achieving vision and goals. Therefore, to ensure implementation of health services, hospitals must conduct an internal performance audit by the Internal Control Unit (SPI) according Under Law No 44 of 2009. This study aims to analyze the implementation of internal supervision in RSUD Tugurejo, Central Java Province. This research used Qualitative Approach in the form of Descriptive Analysis with data collection using in-depth interview method and based on purposive sampling technique. The subjects of the study were all the SPI Tugurejo Regional Hospital of Central Java Province, while the triangulation informants were Deputy Director of Services, service staff, finance staff and general head of the Tugurejo Regional Hospital of Central Java Province. The variables studied by this research appear of human resource, funds, infrastructure/ facility and Regulation (SOP). The results of this study are mechanisms for appointment that have not been well related to the specific competence of internal supervision, have not been facilitated by training for all SPI team personnel related to technical internal supervision, there is no clear and written translation of assignments for each SPI team personnel, internal supervision SPI team personnel, the implementation of internal supervision is more focused on the financial section because the active SPI team is only 2 personnel and both have economic background and lack of employee understanding of the role, function and position of SPI.. This study recommends to the mechanism of appointment through analysis of workload according to the magnitude and complexity of hospital activities, increasing competence by facilitating internal and external training for all SPI team personnel, periodically disseminating information to all employees regarding the role, function and position of SPI for implementation the main tasks and functions of internal supervision can be carried out optimally at the Tugurejo Regional Hospital in Central Java Province.